Evaluasi Sistem Pengendalian Manajemen Terhadap Kualitas Kinerja Jasa Service (Studi Kasus Pada Auto2000 Cabang Rancaekek) - Regita Nissa Ainun; Bunga Sabyla Dwi Rahma; Lieta Chiayu Lestarie (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Health in the corporate body is one aspect that can maintain the sustainability of the company. Including the use of management control system, where control is also one of the operational functions of the company so that expenditures and revenues in accordance with what is targeted. The role of control system is also very important in improving the quality of employee performance and customer satisfaction. The object in this study is PT Astra International, Tbk Auto2000 Rancaekek. This research aims to describe the function of existing management control system can improve the quality of employee work and customer satisfaction. The data source in this study consists of primary data and secondary data collected using interview and observation methods. The collected data is then analyzed descriptively. The results of the study explained that the control system process has been running well, proven by the existence of a very solid and influential work culture, delegation of WWO (Workshop Work Order) well, MTD (Mechanical Task Divider) allocates and organizes mechanical tasks evenly (Heijunka), The head of the workshop gives performance appreciation to employees who reach the target and implement the program in accordance with the previous plan. Keywords: Management Control System, Employee Performance, Corporate Culture